Peran Kantor Wilayah Kementerian Hukum dan Hak Asasi Manusia Terhadap Pendaftaran Indikasi Geografis - Erick Junata Sipayung (Journal of Law and Policy Transformation, 2020)
Indonesia is a country rich in biological natural resources which is spread throughout the region, including the Riau Islands Province. Geographical location surrounded by almost 90% (ninety percent) of the sea area, it indirectly indicates the potential of Geographical Indications that are spread in 7 (seven) districts/ cities in Riau Islands. Directorate General of Intellectual Property through the Regional Office of the Ministry of Law and Human Rights has committed to continue to explore the IG potential in each region determined through the Annual Performance Target. IG legal protection can only be given if an item or product has been registered, for example "Sagu Lingga" which has just been declared as one of the IG products. The registration of “Sagu Lingga” is inseparable from the role of the Regional Office of the Ministry of Law and Human Rights of the Riau Islands in collaboration with the Lingga Regency Government and Indonesian Sagu Empowerment Association of Lingga. From the results of research in the field, in an effort to register potential IG Products in Riau Islands Province, the Role of the Kemenkumham Kepri Regional Office since the enactment of Law Number 20 of 2016 concerning Trademarks and Geographical Indications has not been running optimally, where the form of efforts carried out is still limited to inventory, coordination with local governments and supervision of IG products. This is caused by the existence of several constraints caused by several factors including Legal Factors, Law Enforcement Factors, Means and Infrastructure Factors, Community Factors and also Cultural Factors. Whereas the IG registration effort should aim to establish legal certainty and increase the economic value of a product that has an impact on the welfare of the community. This is what then makes researcher interested in pouring it in the form of research. All information was carried out by unstructured interviews, observations and document studies where sample selection was carried out using the purposive sampling method. The research method used is a sociological juridical research method.